Capacity of myofibrillar protein to adsorb characteristic fishy-odor compounds: Effects of concentration, temperature, ionic strength, pH and yeast glucan addition. (30th November 2021) - Xue, Chao; You, Juan; Zhang, Huimin; Xiong, Shanbai; Yin, Tao; Huang, Qilin
Graphical abstract: Highlights: Off-odors binding to MP were in the order of nonanal > hexanal > 1-octen-3-ol. Off-odors binding to MP were affected by CMP, T, ionic strength, pH and additives. MP adsorption for off-odors reached a maximum at 40 °C and pH 3 or 11. 0.2 M NaCl promoted adsorption of off-odors, while the opposite occurred at 0.6–1.0 M. YG adsorbed off-odors due to its large specific surface area and good stability. Abstract: The capacity of myofibrillar protein (MP) to adsorb fishy-odors (hexanal, nonanal, 1-octen-3-ol) was investigated under the influences of concentration, temperature, pH, ionic strength and yeast glucan (YG) addition. The adsorption of MP for fishy-odors was in the order of nonanal > hexanal > 1-octen-3-ol. With increasing MP concentration, the binding of protein-aldehydes was facilitated, in contrast to a decrease trend in binding to 1-octen-3-ol. Meanwhile, MP adsorption capacity for off-odors peaked at 40 °C. Additionally, low ionic strength (0.2 mol/L) could promote MP adsorption for off-odors, while high ionic strength (0.6–1.0 mol/L) could reduce its adsorption for hexanal and 1-octen-3-ol. Moreover, MP had higher adsorption capacity under extreme pH values (pH 3 and 11). Furthermore, YG was shown as an ideal additive to adsorb off-odors due to its large specific surface area and good stability. This work provides useful information on how to deodorize fishy-odors in fish products.